Efficacy and safety of bevacizumab in combination with docetaxel for the first-line treatment of elderly patients with locally recurrent or metastatic breast cancer: results from AVADO - Pivot, Xavier; Schneeweiss, Andreas; Verma, Shailendra; Thomssen, Christoph; Passos-Coelho, José Luis; Benedetti, Giovanni; Ciruelos, Eva; von Moos, Roger; Chang, Hong-Tai; Duenne, Anja-Alexandra; Miles, David W. (European journal of cancer, 2011)
BACKGROUND: Oncologic treatment in elderly patients is challenging, due to comorbidities, often impaired organ function, limited clinical trial evidence, inadequate guidelines and no consistent 'elderly' definition. We report exploratory sub-analyses of safety and efficacy in elderly patients, defined as ⩾ 65years old, in AVastin And DOcetaxel (AVADO) receiving first-line bevacizumab plus docetaxel for metastatic breast cancer (mBC). - PATIENTS AND METHODS: Patients with HER2-negative, locally recurrent or mBC were randomised to 3-weekly docetaxel (100mg/m(2)) with placebo, bevacizumab 7.5mg/kg or bevacizumab 15 mg/kg, for 9 cycles or until disease progression or unacceptable toxicity. Patients had no prior chemotherapy for mBC. - RESULTS: Progression-free survival (PFS) was increased with bevacizumab in the elderly subpopulation (n=127), the effect being greater with higher dose (hazard ratio=0.63 [95% confidence interval (CI) 0.383-1.032] versus 0.76 [95% CI: 0.46-1.262], respectively). PFS was numerically similar in the elderly and overall populations, but the former failed to achieve statistical significance. Overall response rates for docetaxel plus placebo, bevacizumab 7.5mg/kg and 15 mg/kg were 44.7%, 36.6% and 50.0%, respectively. Effects on survival were not statistically significant. Bevacizumab was well tolerated in elderly patients, the most common adverse effects were neutropenia and febrile neutropenia; there was no excess of grade⩾3 cardiovascular events. There was no clear correlation between baseline hypertension and its development during study treatment. - CONCLUSIONS: In this exploratory sub-analysis in AVADO, bevacizumab plus docetaxel showed efficacy in elderly patients similar to the overall study population. There were no unexpected safety signals in patients aged 65 years or older.